Evaluating retail banking service quality and convenience with MCDA techniques:a case study at the bank branch level - Ferreira, Fernando A. F. (2020)
The intangibility of banking services makes the evaluation of service quality and customer convenience difficult to measure. This paper aims to construct an integrated evaluation system for retail banking service quality and convenience at the bank branch level by combining cognitive mapping with measuring attractiveness by a categorical based evaluation technique. We strive to introduce transparency in the decision making process and add to the performance literature in retail banking. Strengths, weaknesses and practical applications of our multiple criteria evaluation system are also discussed.